Распределение биологической информации в двуспиральной структуре ДНК - Мажуга, П.М. (Вестник зоологии, 1972)
A triplet sequence of DNA chains reduced by a well-known structure of insulin, ribonuclease, lactogenic hormone and haemoglobin testify to the fact that one chain of DNA possesses the function of information of specific biosynthesis. The other chain carries a program realized by means of the first one. In this connection one chain of DNA is defined as a carrying one and the other — as a chain realizing genetic information. So, gene is constructed by the principle of the programe self-controlled by problem and response for one polypeptide. Biological significance of bispiral structure of DNA consists in the possibility of selfreproduction, selfcontrol and self-reduction of the genetic fund.